Profil Kromatografi Lapis Tipis (KLT) Ekstrak Fungi Endofit Akar Kuning (Arcangelisia flava L. Merr.): Thin Layer Chromatography (TLC) Profile of Endophytic Fungi Extract of Arcangelisia flava L. Merr. - Alya Ramadhani; M Arifuddin; Rolan Rusli (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Each plant contains several endophytic fungi that can produce secondary metabolites, one of which is akar kuning plants. This study was conducted to determine the profile TLC of the secondary metabolites separation from the extract of endophytic fungi of akar kuning (Arcangelisia flava L. Merr.). This research began with fermentation of the akar kuning fungi isolate for 14 days. After 14 days, the endophytic fungi biomass and PDB medium were extract by the liquid-liquid extraction method using ethyl acetate as a solvent. Fungi extracts were identified using a thin layer chromatography (TLC) method, observed in UV light of 254 nm, 366 nm and sprayed with dragendorff detection reagent and AlCl3. The identification results with eluent n-hexane: ethyl acetate (3: 1) in 7 spots with Rf values of 0.15; 0.22; 0.35; 0.56; 0.75; 0.85; and 0.95, n-hexane: ethyl acetate (1: 3) produce 6 spots with an Rf value of 0.09; 0.38; 0.67; 0.76; 0.8 ;and 0.85.